Monitoring Road Works Contracts and Unit Costs for Enhanced Governance in Sub-Saharan Africa - Alexeeva, Victoria; Padam, Gouthami; Queiroz, Cesar (World Bank, Washington, DC, 2014)
The study is based on a new specialized dataset generated for the road sector contracts of Bank-financed projects in Sub-Saharan Africa. It is organized as follows: Chapter two describes the data and a set of indicators constructed to perform comparative assessments of the procurement and implementation processes across 13 African countries. Chapter three points out the trends in selected key indicators and performs an inventory of risks for each road works contract using a checklist of possible entry points of corrupt activities or red flags. Through comparison of the road works contracts that had complaints received by the Bank's Department of Institutional Integrity (INT) and other contracts in the sample, it examines if the data exhibit a pattern of indicators consistent with the presence of allegations of corruption or fraud. Chapter four looks at selected issues such as high bid rates, low response to invitation to bid, and cost and time overruns as they were addressed by the project implementing agencies. Finally, chapter five provides selected recommendations to enhance accountability and control of corruption in the road projects financed by the World Bank.